Quantification of Listeria monocytogenes in salad vegetables by MPN-PCR - Ponniah, Jeyaletchumi; Robin, Tunung; S. P., Margaret; Radu, Son; Mohamad Ghazali, Farinazleen; Cheah, Yoke Kqueen; Nishibuchi, Mitsuaki; Nakaguchi, Yoshitsugu; Malakar, Pradeep Kumar (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
The aim of this study was to assess the most probable number-polymerase chain reaction (MPN-PCR) technique for detection of Listeria monocytogenes in salad vegetables in comparison with reference EN ISO 11290-2 and Food Drug Administration Bacteriological Analytical Manual method using artifcial and naturally contaminated samples. Based on recovery of L. monocytogenes from artifcially contaminated samples, MPN-PCR showed a moderate correlation (R=0.67) between spiking concentration and microbial levels which was better than the FDA-BAM method (R=0.642) and ISO 11290-2:1998 method (R=0.655). With naturally contaminated samples, it was found that L. monocytogenes was detected in 25% of the vegetable samples using MPN-PCR; 15% of the samples by the FDA-BAM method and 8% of samples using ISO 11290-2:1998 method. Overall, MPN-PCR was found to be a rapid and reliable method that could facilitate the enumeration of L. monocytogenes in vegetables.